Technical dictionary of heating ventilation, sanitary engineering - Lindeke, Wolfgang (Pergamon Press, 1970)
The four-language technical dictionary covers 5, 300 technical terms in English, Deutsch, French and Russian on heating, ventilation and sanitary engineering.